Insight into β-Hairpin Stability: Interstrand Hydrogen Bonding - Danelius, Emma; Brath, Ulrika; Erdélyi, Máté (Synlett, 2013)
For evaluation of the role of interstrand hydrogen bonding for β-hairpin stability, two cyclic peptides differing only in side chain hydroxy-to-methyl substitution were designed and synthesized on solid phase following the Fmoc–t-Bu–Trt protection strategy. Subsequent to cyclization in solution, combined computational and experimental ensemble analysis revealed higher conformational stability of the peptide capable of interstrand hydrogen bonding.
Keywords: peptides; spectroscopy; macrocycles; β-hairpin; conformation